Bank cards - Ameer, U.A. (JASM, 2010)
The article studying the use of the electronic cards provided by the banks with special reference to credit cards services in comparing with the benevolent loans under the Islamic microfinance concept...
A comparative study between credit cards and the benevolent loan
Keywords: Islamic micro finance